IMPLICATION OF FRACTURE DENSITY ON UNSERPENTINIZED ULTRAMAFIC ROCKS TOWARD CHARACTERISTICS OF SAPROLITE ZONE IN SOROWAKO, SOUTH SULAWESI - Wibowo, Setiyo; Rosana, Mega Fatimah; Haryanto, Agus Didit (Bulletin of Scientific Contribution, 2017)
ABSTRACTUsage of nickel-containing materials has increased over time in accordance with economic growth. The largest worldwide nickel resources occur in surface laterite deposits that have formed during chemical weathering of ultramafic rocks where the area that represent one of largest nickel reserves in Indonesia is Sorowako. This study aims to identify the characteristics of saprolite zone on unserpentinized ultramafic-hosted of nickel laterite deposit in Sorowako. Based on depth profile of nickel content in lateritic deposit, it is known that the Ni grades reach a maximum in saprolite zones so that identification of factors affecting the characteristics of saprolite zone is indispensable. Fracture density on ultramafic bedrocks played the important roles during laterisation and each fractures density type has the implication toward the saprolite zones. By classification of fracture density, high to medium fractured types of bedrocks indicated the thick saprolite zone while the low to unfractured types are thinner. Saprolite zones of high to medium fractured type are more silicified than others due to the originality of silica accumulation occupied along opening fractures and joints. High silica content which is commonly present on lower layer of saprolite zone should to be aware especially when the Ni grade still above the cut-off which potentially affected to ore grade dilution. ABSTRAKPenggunaan material berbahan nikel telah mengalami peningkatan dari waktu ke waktu seiring dengan pertumbuhan ekonomi. Sumberdaya nikel terbesar di dunia terjadi pada endapan laterit di permukaan yang terbentuk selama proses pelapukan kimiawi dari batuan ultramafik dimana salah satu lokasinya dengan tingkat cadangan nikel terbesar di Indonesia berada di Sorowako. Studi ini bertujuan untuk mengidentifikasi karakteristik zona saprolit endapan nikel laterit pada batuan ultramafik tak terserpentinisasi di Sorowako. Berdasarkan profil kedalaman terhadap kandungan nikel pada endapan laterit, telah diketahui bahwa kadar Ni mencapai maksimum dalam zona saprolit sehingga identifikasi terhadap faktor-faktor yang mempengaruhi karakteristik zona saprolit sangat diperlukan. Densitas rekahan pada batuan ultramafik berperan penting selama proses lateritisasi dan setiap tipe densitas rekahan memiliki implikasi terhadap zona saprolit. Melalui klasifikasi densitas rekahan, tipe rekahan berdensitas tinggi hingga sedang pada batuan dasarnya mengindikasikan zona saprolit yang tebal sedangkan zona saprolit pada tipe densitas rekahan rendah hingga tanpa rekahan lebih tipis. Zona saprolit dengan tipe rekahan tinggi hingga sedang lebih tersilisifikasi dibandingkan dengan tipe lainnya disebabkan oleh akumulasi alamiah dari silika yang bertempat di sepanjang bukaan rekahan atau kekar. Kandungan silika tinggi yang umumnya terdapat di lapisan bawah zona saprolit seharusnya diwaspadai terutama ketika kadar Ni-nya masih diatas ambang keekonomian yang berpotensi menyebabkan dilusi pada kadar bijih.